2017
DOI: 10.1002/cmdc.201700550
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship of Propargylamine‐Based HDAC Inhibitors

Abstract: As histone deacetylases (HDACs) play an important role in the treatment of cancer, their selective inhibition has been the subject of various studies. These continuous investigations have given rise to a large collection of pan- and selective HDAC inhibitors, containing diverse US Food and Drug Administration (FDA)-approved representatives. In previous studies, a class of alkyne-based HDAC inhibitors was presented. We modified this scaffold in two previously neglected regions and compared their cytotoxicity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
0
9
0
1
Order By: Relevance
“…43 Intriguingly, follow-up studies indicated thiophene-containing compound 68 was a selective low-nanomolar HDAC6 inhibitor derived from the optimization of 67, whose phenyl linker was replaced by a thiophene ring. 175 15.6 nM) whereas a modest selectivity over HDAC1/8 (Figure 24). After modification, the angle of the rigid linker changed from 180°to 156°, which further influenced the binding models of inhibitor with HDAC6 justified by docking analysis.…”
Section: Hdac6 Inhibitors Bearing Hydroxamic Acid-based Zbgmentioning
confidence: 99%
See 1 more Smart Citation
“…43 Intriguingly, follow-up studies indicated thiophene-containing compound 68 was a selective low-nanomolar HDAC6 inhibitor derived from the optimization of 67, whose phenyl linker was replaced by a thiophene ring. 175 15.6 nM) whereas a modest selectivity over HDAC1/8 (Figure 24). After modification, the angle of the rigid linker changed from 180°to 156°, which further influenced the binding models of inhibitor with HDAC6 justified by docking analysis.…”
Section: Hdac6 Inhibitors Bearing Hydroxamic Acid-based Zbgmentioning
confidence: 99%
“…On the other hand, the angle of the rigid linker can be modified by the use of five-membered heteroaromatic moieties (Figure 22) and may result in novel conformations and binding models with the HDAC6 active site. 175 For the first time, Jung et al performed detailed SAR studies on HDAC6 inhibitors involving three different heterocycles, oxazole, thiazole, and oxadiazole, that were attached to the hydroxamate moiety. 176 Work begun with a virtual screening, by which compound 64 (IC 50 = 300 nM) employing a thiazolebased linker was determined as a potential lead for the next optimization (Figure 23).…”
Section: Hdac6 Inhibitors Bearing Hydroxamic Acid-based Zbgmentioning
confidence: 99%
“…Intramolecular Pauson–Khand reaction [ 14 ], Diels–Alder reaction [ 15 ], gold-catalyzed azetidin-3-one formation [ 16 ], as well as various transition metal-mediated additions and cross-coupling reactions [ 17 ] represent further important reactions of propargylamines, providing the potential to form innovative peptidomimetics ( Fig. 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…c) Gold-catalyzed intramolecular reaction to azetidin-3-ones, R = tert -butylsulfonyl, R’ = aromatics, aliphatics [ 16 ]. d) Sonogashira cross-coupling, R = tert- butylsulfinyl, R’ = Me, CHMe 2 , CH 2 CHMe 2 , cyclohexyl [ 17 ]. e,f) Cu I or Ru II -catalyzed [3 + 2] cycloadditions (CuAAC, RuAAC) [ 18 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Em meados de 1960, o primeiro artigo sobre propargilaminas foi publicado e, desde então, esses compostos vêm sendo utilizados, 40 pois são estruturas chaves de produtos naturais e farmacêuticos, sendo estes β-lactamas, análogos de oxotremorina, peptídeos e isósteros (Figura 4). 41,42 Além disso, propargilaminas são estruturas privilegiadas por inibirem enzimas que estão diretamente relacionadas com o Alzheimer. Lauder, K.;Toscani, A.;Scalacci, N.;Castagnolo, D. Chem.…”
Section: Reações Multicomponentesunclassified